Analisis Sentimen Komentar SIAKAD Menggunakan Metode Naive Bayes Classifier - Kaka, Dualu Lado; Pati, Gergorius Kopong; Rato, Karolus Wulla (Jurnal Kridatama Sains dan Teknologi, 2023)
In all industries, information and communication technology is expanding very quickly. All administrative tasks have ramifications that genuinely call for technology. When the innovation successfully mixes technology with information, the position of this technology becomes increasingly significant. Information technology has permeated so deeply into even the most insignificant aspects of human life, such as the use of academic information systems (SIAKAD) in raising the caliber of academic services, that there are many users who use it in their daily lives who have witnessed an acceleration of change that was previously unimaginable. Public sentiment was categorized and then used to conduct the analysis. The Navie Bayes Classifier is the main technique applied in this study. To assess the degree of accuracy, a comparison will be made using this approach. Positive and negative emotions are classified as sentiments. The purpose of this study is to tell the public about SIAKAD by utilizing student feedback and understanding the degree of accuracy of the techniques examined for method comparison. The test results will undergo method testing and accuracy testing using the Rapidminer tool.Keywords: Navie Bayes Classifier, SIAKAD